Education Transformation: The Impact of Digital Mindset on Chemistry Teacher Innovation - Amalia, Ilmi Zakiah; Sari, Eliana; Ahmad, Masduki (Universitas Negeri Malang, 2024)
Abstract: This study aims to analyze the influence of a digital mindset on the innovative behavior of chemistry teachers. A digital mindset, which reflects teachers' readiness and ability to utilize digital technology, is a key factor in driving innovation in education. Innovation among chemistry teachers includes creativity in teaching methods, the use of technology in the classroom, and the application of teaching approaches relevant to 21st-century needs. The technique used is a quantitative survey. The sample of this study consists of 60 chemistry teachers. Data collection techniques use a Likert scale questionnaire with five response options: Always, Often, Sometimes, Rarely, and Never. Data analysis is performed using SEM with the help of the SmartPLS 3.0 program. The results of the study show a coefficient value of 0.862 with a p-value of 0.000 < 0.05 and a t-value of 32.794 > 1.96, indicating that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted, signifying a significant influence of digital mindset on teachers' innovative behavior. Teachers with a well-developed digital mindset are more likely to utilize digital tools, engage in ongoing professional development, and collaborate with their peers to share best practices. These behaviors lead to more effective and engaging teaching strategies, ultimately enhancing student understanding and motivation. Despite potential obstacles such as limited training and resources, fostering a digital mindset among chemistry teachers is crucial for advancing educational practices and improving the quality of learning experiences. Therefore, the digital mindset affects the innovative behavior of chemistry teachers. The implications of this study highlight the importance of training and strengthening the digital mindset among teachers to support educational transformation. Training programs focused on improving technological skills and understanding digital pedagogy should be prioritized to create innovative learning environments that adapt to evolving times. Keywords: Digital Mindset, Innovative Behavior, Chemistry Teachers, Education Management